2018
DOI: 10.1101/303982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catecholamine Challenge Uncovers Distinct Mechanisms for Direct Versus Indirect, but Not Social Versus Non-Social, Learning

Abstract: 1Evidence that social and individual learning are at least partially dissociable sustains the belief that 2 humans possess adaptive specialisations for social learning. However, in most extant paradigms, 3 social information comprises an indirect source that can be used to supplement one's own, direct, 4 experience. Thus, social and individual learning differ both in terms of social nature (social versus 5 non-social) and directness (indirect versus direct). To test whether the dissociation between social 6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Their research with this non-social control has revealed domain-specific processing but not for the social domain. They have shown that indirect learning differs from direct learning (Cook et al, 2018), and that meta-learning differs from first-order learning (Cook et al, 2019), but they have not found that different models fit the data when people believe they are getting information from other agents rather than rigged roulette wheels (Cook et al, 2018).…”
Section: The Mentalist Casementioning
confidence: 99%
See 1 more Smart Citation
“…Their research with this non-social control has revealed domain-specific processing but not for the social domain. They have shown that indirect learning differs from direct learning (Cook et al, 2018), and that meta-learning differs from first-order learning (Cook et al, 2019), but they have not found that different models fit the data when people believe they are getting information from other agents rather than rigged roulette wheels (Cook et al, 2018).…”
Section: The Mentalist Casementioning
confidence: 99%
“…A more reliable way of solving the social specificity problem is to use contrastive experiments with an 'inanimate' or 'non-social' control condition (Cook et al, 2014(Cook et al, , 2018Heyes, 2014aHeyes, , 2014bLockwood et al, 2020). Cook and colleagues have pioneered this approach in studies of social learning.…”
Section: The Mentalist Casementioning
confidence: 99%